Anatomical and Technical Considerations in Fascicular Nerve Transfers for Foot Drop - Seruya, Mitchel (Journal of Reconstructive Microsurgery, 2024)
Background Foot drop is the common endpoint for a diverse set of nerve injuries, affecting over 128,000 in the United States each year. The level of injury, finite pace of regeneration, and/ exponential decay in the percentage of motor end-plates reinnervated over time may explain the limited success with natural recovery. Past nerve techniques have also been met with limited success.Methods This narrative review explores why past nerve techniques have failed to correct foot drop.Results Previously described nerve transfer techniques suffer from incompletely balancing the foot and ankle, poor donor-target nerve synergy, and/or not effectively bypassing the wide and oftentimes underappreciated zone of injury. For maximal stability, one should look to balance the foot in both dorsiflexion and eversion. Detailed descriptions and illustrations of the branching anatomy for the peroneal and tibial nerves are provided, with specific application to nerve transfer reconstruction.Conclusion Based on an understanding of why past nerve techniques have failed to correct foot drop, a set of surgical principles can be codified to optimize functional outcomes. A surgical technique should be versatile enough to address foot drop from any of the three common pathways of injury (lumbar spine, sciatic nerve, and common peroneal nerve). With increasing familiarity using this once poorly understood anatomical region, limitations with past nerve transfer techniques may be overcome.
Keywords: foot drop; sciatic nerve palsy; common peroneal nerve palsy; nerve transfer; peroneal nerve palsy; tibial nerves